2020 4th Scientific School on Dynamics of Complex Networks and Their Application in Intellectual Robotics (DCNAIR) 2020
DOI: 10.1109/dcnair50402.2020.9216804
|View full text |Cite
|
Sign up to set email alerts
|

Spatial memory based on an STDP-driven neural network

Abstract: We propose a model of spatial memory implemented in a Spiking Neural Network (SNN) and test it on a robot moving in an environment with neutral and harmful regions. Neurons in the SNN play the role of place cells, and their population dynamics determines the robot movements. We show that STDP rearranges the couplings in the SNN and forms spatial memory similar to cognitive maps associated with the negative experience. Then, the robot learns to avoid harmful zones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…The publication by Zharinov et al [104] showed the model of spatial memory implemented on SNN. This model was then tested on a robot moving in an environment with neutral and harmful regions.…”
Section: Speech Recognitionmentioning
confidence: 99%
“…The publication by Zharinov et al [104] showed the model of spatial memory implemented on SNN. This model was then tested on a robot moving in an environment with neutral and harmful regions.…”
Section: Speech Recognitionmentioning
confidence: 99%